Isolation and molecular-based identification of bacteria from unhatched leftover eggs of ducks in selected mini-hatcheries of Kishoreganj, Bangladesh - Punom, Sadia Afrin; Khan, Md Shahidur Rahman; Pritha, Shayka Tasnim; Hassan, Jayedul; Rahman, Saifur; Mahmud, Md Muket; Islam, Md Shafiqul (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: The study was designed for isolation and identification of the bacteria present in unhatched leftover eggs of duck in selected mini-hatcheries of Kishoreganj, Bangladesh. Materials and Methods: A total of 54 unhatched discarded eggs were collected as samples from different mini-hatcheries of Tarail and Itna Upazilas of Kishoreganj and aseptically carried to the laboratory in the icebox. Surface washings (n = 54) and inner contents (n = 54) were collected and enriched in Luria–Bertani broth followed by the isolation of pure colonies of different bacteria onto eosin methylene blue agar, mannitol salt agar, Salmonella–Shigella agar, and blood agar plates. Identification of the bacterial isolates was done by cultural properties, staining, and biochemical tests followed by molecular detection by Polymerase chain reaction. Results: Of 108 samples, 62 were found positive for Salmonella spp. (76%), 59 for E. coli (54%), 52 for Staphylococcus spp. (48%), and 5 for Clostridium spp. (9%). From the egg surface samples, Staphylococcus spp. were recovered in the highest (67%) followed by Salmonella spp. (59%), E. coli (56%), and Clostridium spp. (9%). From the inner contents of eggs, Salmonella spp. were recovered in the highest (56%), followed by E. coli (53%) and Staphylococcus spp. (30%). Conclusion: The isolated bacteria might be associated with the decreased hatchability and embryo mortality in the mini-hatcheries of duck. J. Adv. Vet. Anim. Res., 7(1): 164-169, March 2020